SPOTLIGHT on 1986 Brigadier Stokes Award - H. Wagner (The Southern African Institute of Mining and Metallurgy, 1986)
In 1980 The South African Institute of Mining and Metallurgy instituted the Brigadier Stokes Memorial Award to commemorate the outstanding contribution to the South African mining industry made by Brigadier R.S.G. Stokes, who was an Honorary Life Fellow and a Past President of the Institute.